Ecological and Social Justice as Basis on Marine Environment Protection and Preservation in The System of Indonesian Law - Purwendah, Elly Kristiani; Djatmiko, Agoes; Erowati, Eti Mul; Triana, Ikama Dewi Setia; Pudyastiwi, Elisabeth (Universitas Negeri Malang, 2022)
This study aimed to determine ecological and social justice as the basis for protecting and preserving the marine environment in the Indonesian legal system. This research was empirical normative legal research. The subject of the study was the implementation of favourable legal provisions in every particular legal event that occurred in society to achieve the predetermined goals. If not careful in its application (still characterized by anthropocentrism), this political economy policy could conflict with the social ecology currently developing in Indonesia through the concept of a green economy and a blue economy. The characteristics of the socialism system in the political economy related to environmental justice after the amendment to the 45th Constitution began to shift in the era of globalization so that it began to respond to ecological modernization. However, due to colliding with the concept of socialism, the ecological justice system in the Indonesian legal system had the nuances of social-ecological justice. This concept would significantly affect the fairness of compensation for oil pollution by tanker accidents in Indonesia.